Desamparo aprendido com o zebrafish (Danio rerio) - NASCIMENTO, Gabriela Souza do (Universidade Federal do Pará, 2018)
Exposure to uncontrollable aversive events leads to difficulty in learning contingency relations, escape and/or avoidance. Such phenomenon was named learned helplessness and it has been correlated to depression and post-traumatic stress disorder. This thesis is composed by three studies that together have the aim of: producing learned helplessness in Danio rerio (Study I); investigating the effects of light on the escape test (Study II) and evaluating the effects imipramine have on learned helplessness when applied acutely in Danio rerio (Study III). In every experiment it was used an acrylic shutllebox (INSIGHT equipment) which contained a central area (removable) that enabled the isolation of the subjects. The general protocol consisted in two phases: 1) Treatment, each subject of the Uncontrollable shock (USH) treatment was subjected to 60 random and uncontrollable shocks (0.7 – 0.9V, lasting 30 seconds each), in this phase the subjects of the group that didn't receive treatment with electric shock (NSH) only remained in the central area for 60 minutes; and 2) Test, each subject from both groups was subjected to an escape session with 30 shocks (0.7 – 0.9V, maximum duration of 30 seconds each). In Study I, 3 groups were used, one experimental (EGUSH) and two controls, one remaining in the experimental aquarium for 60 minutes without shock (CG-NSH). In Study II, 4 groups were used, a pair from NSH and USH subjected to the light test, another pair (NSH and USH) underwent the test no light condition. In Study III 6 groups were used according to the concentration of imipramine administered during 10 minutes before the test session: 0.0 mg/l NCH; 0.0 mg/CHI; 1.0 mg/l NCH; 1.0 mg/l CHI; 2.0 mg/l NCH; e 2.0 mg/l CHI. The main results show that it is possible to create learned helplessness in Danio rerio (study I), considering light as a variable that can interfere directly in the acquisition of the phenomenon (study II), in addition, it was showed that acute imipramine in the doses administered here did not revert the learned helplessness in Danio rerio.